Nodular fasciitis: a rare case report type of article - Gedam, Bapuji S.; Sadriwala, Quraysh S.; Kulkarni, Nikita J. (International Surgery Journal, 2017)
Nodular fasciitis is defined as a benign and reactive fibroblastic growth extending from the superficial fascia into the subcutaneous tissue or muscle. It is a rare benign neoplasm most commonly afflicting the soft tissues of upper extremity followed by trunk, head, and neck. It accounts for 0.025% of all pathologic diagnosis. We report a case of a swelling over the right scapula which on cytology examination was diagnosed as a benign spindle cell lesion. It was subsequently confirmed to be an intramuscular nodular fasciitis on histopathological examination.